ANALYZING COSMIC RAY MODULATION BASED ON SOLAR ACTIVITY AND INTERPLANETARY PLASMA PARAMETER VARIATION - Novia Indra Putri, Annisa
A correlation between cosmic ray intensity with 11 solar and interplanetary parameters has been made. We used modulation of cosmic ray intensity observed at four different stations with different latitude and cut-off rigidity. PLS method was used to rank parameters and will be compared to PCA method. PLS methods results show that the parameters sunspot number, IMF, HCS, and plasma velocity contribute a more substantial influence on the modulation of cosmic ray intensity in all cases and all stations based on the magnitude of the first component. In case of the influence of CME halo type, the important parameters were sunspot number, IMF, HCS, CME speed, and proton density. During solar energetic particle event, the significance parameters were sunspot number, IMF, HCS, SPEs, and plasma velocity. The fourth case was tested using the PCA method and show similar result with PLS method. Sunspot number, IMF, HCS, CME speed, and proton density parameters are strong parameter making effect cosmic ray modulation. We also tried to analyze it at the PSNM station and got different results. The By, Bx, and cone angle parameters are strong in influencing cosmic ray intensity modulation in both methods. This is possible because the influence of these parameters on cosmic ray modulation depends on the latitude. These results will be analyzed using the MHD simulation method. The experimental MHD simulation was carried out in Carrington Rotation (CR) 2009 and 2179 where in CR 2009 there was a Halloween storm while CR 2179 was to cover data from PSNM stations. As a result, the parameters density, speed, and magnetic field have a clearer correlation than temperature to cosmic rays. This strengthens the evidence that most cosmic ray variations are influenced by the strong parameter.